Integrated Management of Meloidogyne incognita and Soilborne Fungi Infecting Cucumber under Protected Cultivation - Patil J. A.; Yadav Saroj; Ram Sewak; Kumar Anil; Kumar Satish (Journal of Nematology, 2022)
Relative efficacy of various approaches for management of Meloidogyne incognita and the soilborne fungus Fusarium oxysporum f. sp. cucumerinum has been tested in cucumber under protected cultivation conditions for two seasons. Management practices, namely, chemicals (fumigant, nonfumigant, and fungicide), organic amendments (neem cake, leaves, and oil opted as soil and seed treatment), and biocontrol agents (egg-parasitic fungus and Purpureocillium lilacinum), were combined for the management of the disease complex in a randomized block design. Two significant parameters were measured: plant growth parameters (shoot length, dry shoot weight, dry root weight, and yield) and disease parameters (galls per plant, final nematode population, egg masses per plant, and fungal incidence). All treatments significantly improved plant growth parameters and reduced nematode reproduction as compared to untreated check. The integration of formalin and neem oil seed treatment favors the low root galling index compared to all other treatments in both the seasons. Formalin and neem oil seed treatment reduced the nematode population and fungal incidence, and increased the yield of cucumber during both the seasons.